2022
DOI: 10.5306/wjco.v13.i6.473
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA for diagnosis, prognosis and treatment of gastrointestinal malignancies

Abstract: Minimally invasive detection of circulating tumor DNA (ctDNA) in peripheral blood or other body fluids of patients with gastrointestinal malignancies via liquid biopsy has emerged as a promising biomarker. This is urgently needed, as conventional imaging and plasma protein-derived biomarkers lack sensitivity and specificity in prognosis, early detection of relapse or treatment monitoring. This review summarizes the potential role of liquid biopsy in diagnosis, prognosis and treatment mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Multiple techniques, such as real-time quantitative polymerase chain reaction (qPCR), digital droplet PCR (ddPCR), and next-generation sequencing (NGS), have been utilized for the detection and analysis of ctDNA [ 26 ]. The detection of ctDNA can either be targeted or untargeted, while DNA may enter the bloodstream through both active and passive mechanisms [ 27 , 28 , 29 , 30 ].…”
Section: Overview Of Liquid Biopsies: Ctdnamentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple techniques, such as real-time quantitative polymerase chain reaction (qPCR), digital droplet PCR (ddPCR), and next-generation sequencing (NGS), have been utilized for the detection and analysis of ctDNA [ 26 ]. The detection of ctDNA can either be targeted or untargeted, while DNA may enter the bloodstream through both active and passive mechanisms [ 27 , 28 , 29 , 30 ].…”
Section: Overview Of Liquid Biopsies: Ctdnamentioning
confidence: 99%
“…The ratio between ctDNA and cfDNA can greatly vary anywhere between 1 and 40% due to the characteristics of the primary tumor as well as the presence and location of metastatic disease [17,20,25]. Multiple techniques, such as real-time quantitative polymerase chain reaction (qPCR), digital droplet PCR (ddPCR), and next-generation sequencing (NGS), have been utilized for the detection and analysis of ctDNA [26]. The detection of ctDNA can either be targeted or untargeted, while DNA may enter the bloodstream through both active and passive mechanisms [27][28][29][30].…”
Section: Overview Of Liquid Biopsies: Ctdnamentioning
confidence: 99%
“…First, the patient's Signatera™ testing was drawn using a mobile phlebotomy station, highlighting improved convenience. Previous studies have indicated that ctDNA changes often precede observable changes on imaging [ 40 ]. Given the positive ctDNA assay and positive imaging findings, a negative ctDNA assay could potentially lead to less frequent imaging and change the standard of care.…”
Section: Completed Trialsmentioning
confidence: 99%
“…We read with great interest the minireview by Kirchweger et al [ 1 ], entitled “Circulating tumor DNA (ctDNA) for diagnosis, prognosis and treatment of gastrointestinal malignancies”. This paper provides a comprehensive overview on available literature data regarding the potential role of ctDNA in the management of gastric, biliary tract, liver, pancreatic and colorectal cancer (CRC).…”
Section: To the Editormentioning
confidence: 99%